New SHRIMP U–Pb zircon ages and CHIME monazite ages from South Harris granulites, Lewisian Complex, NW Scotland: Implications for two stages of zircon formation during Palaeoproterozoic UHT metamorphism - Baba, S.; Dunkley, Daniel; Hokada, T.; Horie, K.; Suzuki, K.; Shiraishi, K. (Elsevier BV, 2012)
Sensitive high-resolution ion microprobe (SHRIMP) U–Pb zircon age dating was applied to several types of granulites and gneisses from the Lewisian Complex in South Harris, NW Scotland, to clarify the timing of Palaeoproterozoic tectono-thermal events. For comparison, monazite was dated using the chemical Th–U–total Pb isochron method (CHIME). The obtained U–Pb zircon age data were evaluated under the constrains of the modal amount of constituent minerals and whole-rock compositions of analysed samples, the zircon internal texture based on Th/U ratios, and the monazite CHIME ages. Zircons in three samples, characterised by zoned overgrowth rims, sector-zoned grains, and structureless high-U cores, yielded concordant ages of approximately 1900 Ma (1909 ± 3 Ma, 1899 ± 10, and 1888 ± 15 Ma, respectively). The age of 1899 ± 10 Ma, obtained from melanocratic granulite (garnet and kyanite/sillimanite: 76–91 vol.%), is interpreted to represent the timing of zircon crystallisation prior to the formation of restitic garnet and kyanite/sillimanite.Therefore, the age of ∼1900 Ma is proposed to represent the timing of early metamorphism, close to the thermal peak (M1). In the leucocratic gneiss (sample 93921-7), the age population at 1868 ± 35 Ma obtained from low-U and low-Th overgrowth rims represents a second stage of zircon growth from crystallising anatectic melt (M3), whereas the high-U cores represent the timing of zircon growth and recrystallisation prior to anatexis. Monazites from two leucocratic gneisses yield a relatively narrow range of CHIME ages: 1858 ± 7 Ma and 1840 ± 7 Ma. These ages probably represent the timing of zircon and monazite crystallisation from partial melt and resetting of the U–Th–Pb system. These results suggest that the timing of zircon formation was controlled by metamorphic processes, such as restite formation and crystallisation from partial melt.